Assessment of the right ventricle in donation after circulatory death hearts. Issue 3 (20th October 2020) - Kadowaki, Sachiko; Kotani, Yasuhiro; Kobayashi, Yasuyuki; Goto, Takuya; Kasahara, Shingo
Abstract: In donation after circulatory death heart transplantation, the donor heart is exposed to circulatory load. The right ventricle, due to its structure, has high compliance for volume load but is particularly vulnerable to increased pressure load. This study used a porcine model to conduct a functional assessment of the hemodynamics of the heart, with a focus on the right ventricle. Six pigs weighing 24.6 ± 1.4 kg were used. Circulatory death was induced by asphyxiation after median sternotomy. After 30 minutes in the state of global warm ischemia, the ascending aorta was clamped, followed by a 20‐minute reperfusion of the heart with a 20°C blood cardioplegia solution. Systemic circulation was established by cardiopulmonary bypass after aortic cross‐clamping. After initial reperfusion, the blood cardioplegia solution was replaced with blood. The blood was then rewarmed while the heart was still in a non‐working state. Cardiac function was assessed twice in situ, first by the thermodilution method, and then, by the pressure–volume measurement both at preischemia and at three hours after initiation of reperfusion. The recovery rate of cardiac output was 75%. End‐systolic elastance ( P  = .02) and pulmonary arterial elastance significantly increased ( P  = .03), but the ratio of arterial elastance to end‐systolic elastance was preserved ( P  = .91) in the right ventricle. Despite a decrease in cardiac output after reperfusion from warm ischemia, the right ventricle had a potential to respond the elevated afterload. It is important that donations after circulatory death heart transplantation should be performed with attention to avoiding right ventricular distension. Abstract : The cardiac output after reperfusion was 75% of the baseline value in the right ventricle of the donation after circulatory death porcine model. The ratio of arterial elastance to end‐systolic elastance did not show significant difference compared to the baseline value, thus the right ventricle had a potential to respond the elevated afterload at the acute phase after reperfusion.